Interactions of Streptococcus suis serotype 9 with host cells and role of the capsular polysaccharide: Comparison with serotypes 2 and 14. - Jean-Philippe Auger; Servane Payen; David Roy; Audrey Dumesnil; Mariela Segura; Marcelo Gottschalk (PLoS ONE, 2019)
Streptococcus suis is an important porcine bacterial pathogen and a zoonotic agent responsible for sudden death, septic shock and meningitis, of which serotype 2 is the most widespread, with serotype 14 also causing infections in humans in South-East Asia. Knowledge of its pathogenesis and virulence are almost exclusively based on these two serotypes. Though serotype 9 is responsible for the greatest number of porcine cases in Spain, the Netherlands and Germany, very little information is currently available regarding this serotype. Of the different virulence factors, the capsular polysaccharide (CPS) is required for S. suis virulence as it promotes resistance to phagocytosis and killing and masks surface components responsible for host cell activation. However, these roles have been described for serotypes 2 and 14, whose CPSs are structurally and compositionally similar, both containing sialic acid. Consequently, we evaluated herein the interactions of serotype 9 with host cells and the role of its CPS, which greatly differs from those of serotypes 2 and 14. Results demonstrated that serotype 9 adhesion to but not invasion of respiratory epithelial cells was greater than that of serotypes 2 and 14. Furthermore serotype 9 was more internalized by macrophages but equally resistant to whole blood killing. Though recognition of serotypes 2, 9 and 14 by DCs required MyD88-dependent signaling, in vitro pro-inflammatory mediator production induced by serotype 9 was much lower. In vivo, however, serotype 9 causes an exacerbated inflammatory response, which combined with persistent bacterial presence, is probably responsible for host death during the systemic infection. Though presence of the serotype 9 CPS masks surface components less efficiently than those of serotypes 2 and 14, the serotype 9 CPS remains critical for virulence as it is required for survival in blood and development of clinical disease, and this regardless of its unique composition and structure.